The To-day and To-morrow Series and the Popularization of Science: An Introduction - Saunders, Max; Hurwitz, Brian (Interdisciplinary science reviews, 2009)
There can be few people as influential in scientific publishing in the early twentieth century as Charles Kay Ogden. In 1920, he helped found the journal @@iPsyche@, which he edited. He also acted as editor for several ambitious book series for the publishers Kegan Paul, Trench, Trubner and Co. In 1922, he launched The International Library of Psychology, Philosophy and Scientific Method, which ran to around one hundred and fifty volumes -- it was later extended into Routledge's International Library of Philosophy -- starting with Wittgenstein's @@iTractatus@ (which Ogden had helped translate), and including landmark works by Carnap, Husserl, Piaget, Malinowski, Jung, and W. H. R. Rivers. From 1926, he also oversaw a series of Psyche Miniatures, which ran to over one hundred volumes. In between, he edited the more speculative series that is the subject of the essays discussed in this issue: To-day and Tomorrow. It too included more than a hundred titles, on an extremely wide range of topics of contemporary interest, published between 1923 and 1931 (though there was an attempt to relaunch the series in 1936, with half a dozen revised and expanded titles).